Marketing Politik dan Strategi Pemenangan Pemilu - Roni Tabroni (Universitas Swadaya Gunung Djati, 2013)
In the midst of the political development of the country, a new phenomenon emerged in the context of the campaign. As has been done in some developed countries, politics are now both in terms of both academic and practical studies, other studies have involved the better known political marketing. Political marketing corelation with the process of political socialization either political party or candidate legislative or regional head and the President, in order to be recognized and selected by the public. Therefore, political marketing strategy in relation to political competition. With political marketing, patterns of socialization involves not only political elements, but the communication and business. The purpose of this socialization is introduced the political party and its candidates to convince people to choose from at the time of election, or presidential elections. Included is how political marketing can also restore the image of a political party that has a negative image in public Keyword: Political Marketing, Political Party, Demokracy